25.3k views
3 votes
If s ( x ) = 2 - x² and t ( x ) = 3x, what is s ( t ( -7 ) )?

User Timo Ernst
by
5.0k points

1 Answer

0 votes

Answer:

- 439

Explanation:

  • s ( x ) = 2 - x²
  • t ( x ) = 3x
  • s ( t ( -7 ) ) = ?

--------------------------

  • t (-7) = 3 * ( -7 ) = -21
  • s ( t ( -7 ) ) = s ( -21 ) = 2 - ( -21 )² = 2 - 441 = - 439
  • s ( t ( -7 ) ) = -439
User Pzaenger
by
5.3k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.